(untitled) (Acta Scientiarum. Biological Sciences, 2013)
The broad-snouted caiman, Caiman latirostris, is widely distributed in countries of South America. In Brazil it is considered an endangered species because of natural habitat destruction and illegal hunting. In reptiles, the thyroid gland plays an integral part in ecdysis, reproduction, tail regeneration, growth, endocrine function and metabolism rate. The aim of the present study was to characterize the thyroid gland morphology of C. latirostris, based on histochemical and immunohistochemical techniques. The thyroid glands were fixed in Bouin’s fluid and serial cross sections were stained with hematoxylin-eosin, Mallory’s trichrome, periodic acid-Schiff (PAS) and Alcian blue (AB pH 1.5 and 2.5). The immunohistochemical technique for 5-HT-IR cells was used. The thyroid gland has a dense irregular connective tissue forms a capsule enveloping the gland. There are several follicular acini of varying size lined by simple cuboidal or columnar epithelium in the thyroid gland. The follicles are connected by interfollicular connective tissue which contains blood vessels. We observed the presence of lymph nodes around the entire gland. There was a positive PAS reaction and negative AB reaction in the colloid. 5-HT-IR cells were detected around the follicle cells. No striking morphological differences were observed between C. latirostris and other domesticated mammals.